Social network model based on the transmission of information - Yan-heng LIU; Fei-peng LI; Xin SUN; Jian-qi ZHU (Tongxin xuebao, 2013)
The topology modeling of the social network is propitious to understanding the transmission process of information and the topology characteristic of the real friendship network.Considering the directed characteristic of information spread,the dynamic process of information dissemination was simulated,and moreover,the weighted directed topology model in order to well emulate the topology structure of the social network was constructed.Simulation results show the degree and strength distribution as well as the correlation between degree and strength of the network generate by the topology model embody obvious power-law characteristic,and meanwhile,through analyzing the clustering coefficient,coreness and Gini coefficient of the network,the generated network has the characteristics of clustering,layer and heterogeneity which are shown in the real friendship network is verified.